Ambient scent as a mood inducer in supermarkets: The role of scent intensity and time-pressure of shoppers. (May 2019) - Leenders, Mark A.A.M.; Smidts, Ale; Haji, Anouar El
Abstract: This research aims to study the effect of a carefully selected congruent and simple ambient scent in a real-world supermarket setting. Specifically, we study how different levels of scent intensity affect shopper's mood, behavior and evaluations in a space with naturally occurring scents. Using electrostatic aroma diffusers, we apply a carefully selected melon scent at three different intensity levels in a large store of a major supermarket operator. The results show that, in the condition with high scent intensity, the scent has a significant positive effect on shopper's store evaluations, time spent in store and store level sales. We provide evidence that mood is, as expected, a strong mediator of the effect of scent on positive evaluations. We also find that scent, used as a mood inducer, is especially effective for hurried shoppers. Interestingly, in terms of general mood inducement, we find that shoppers tend to overestimate the amount of time spent shopping at lower intensity levels and underestimate time spent shopping at high scent intensity levels. Implications for marketing and store management are discussed.